Astronavigation-level energetic protective structural slab and preparation method thereof

By combining polymer matrix materials and impact response agents, the spacecraft protection structure has been solved, and the spacecraft protection structure has been large, poor protection effect and insufficient radiation resistance, and lightweight, effective protection and high radiation performance have been achieved. It is suitable for spacecraft applications that resist centimeter-level space debris and long-term radiation.

CN119242042APending Publication Date: 2025-01-03CHINA ACADEMY OF SPACE TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411512736.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing spacecraft protective structure materials have large weight and poor protection effect, making them difficult to effectively withstand the impact of centimeter-level space debris, and lack of radiation resistance, which violates the development trend of low-cost and lightweight.

Method used

Aerospace-grade energy-containing protective structural panels that combine polymer matrix materials with impact responders are used to achieve active use of the gas or heat generation effect of impact responders through the combination of polyimide resin, high-energy oxidizer and metastable active material. Protect and improve material density and radiation resistance through polymer cross-linking curing.

Benefits of technology

On the premise of ensuring lightweight, the protective effect and radiation resistance of the protective structural panel are significantly improved, which is better than aluminum alloys of the same thickness, which can effectively resist high-speed impacts and long-term radiation, and meet the long-life needs of spacecraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242042A_ABST
    Figure CN119242042A_ABST
Patent Text Reader

Abstract

The invention provides an astronavigation-level energetic protective structural slab and a preparation method thereof, the astronavigation-level energetic protective structural slab comprises a polymer matrix material and an impact response agent, the mass percentage of the polymer matrix material is 80-95%, and the mass percentage of the impact response agent is 5-20%; the polymer matrix material is polyimide resin; the impact response agent is selected from at least one of 5, 5 '-bistetrazole-1, 1'-dioxodihydroxyammonium or trinitrotoluene, or the impact response agent comprises a high-energy oxidant and a metastable state active material, and the high-energy oxidant is selected from at least one of manganese dioxide, ferric oxide, copper oxide or potassium permanganate; the metastable active material is selected from at least one of aluminum powder, magnesium powder or boron powder. The protective structural plate has the characteristics of low density, good protective effect, high and low temperature resistance and high space irradiation performance, and the space application reliability of a protective material is ensured while the weight is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of protective structural plates, and in particular relates to an aerospace-grade energetic protective structural plate and a preparation method thereof. Background Art

[0002] Spacecraft are constantly threatened by hypervelocity collisions with space debris during long-term orbital operation. In particular, the large number of launch missions by various countries in recent years has caused a sharp increase in space debris, leading to a further deterioration of the space environment. According to statistics from the US Space Monitoring Network, there are currently more than 500,000 pieces of space debris larger than 1 cm and more than 35 million micrometeoroids / space debris larger than 1 mm. In the next 200 years, if the current normal frequency of spacecraft launches is maintained, the number of space debris larger than 10 cm may increase by 100,000 by 2210.

[0003] In order to reduce the threat of space debris to spacecraft, relevant research institutions in my country have been committed to the design and development of spacecraft protection structures in recent years. After years of research, a variety of spacecraft protection structures have been designed, including multi-layer impact protection structures, corrugated protective screen protection structures, mesh protection structures, flexible deployable protection structures, etc. The main protective materials used are aluminum alloy, honeycomb panels, foam aluminum, basalt fiber cloth, etc. However, all protective structural materials are inert materials. Due to the single protection mechanism, when facing the impact of hypervelocity space debris, the only way to enhance the protection effect is to simply increase the thickness of the protective material, which directly causes the weight of the spacecraft to increase, resulting in increased launch costs and increased launch difficulty. This is also inconsistent with the development trend of low-cost and lightweight aerospace in my country.

[0004] The size of protective devices has strict requirements, which largely restricts the protective effect of protective structures against large-sized debris. Currently, commonly used protective structures can basically only withstand impacts with space debris smaller than 1 cm. In recent years, with the continuous increase of centimeter-level space debris, the probability of spacecraft failure due to impact has increased significantly, which has posed new challenges to the spacecraft's space debris protection capabilities. The design of new protective structures that can resist centimeter-level space debris has become an urgent need. Summary of the invention

[0005] In order to overcome the deficiencies in the prior art, the inventors have conducted intensive research and provided a space-grade energetic protective structural plate and a method for preparing the same, which solves the problems of heavy weight of current metal protective materials, poor protective effect of traditional polymer materials, and poor tolerance to space radiation. The protective structural plate has the characteristics of low density, good protective effect, resistance to high and low temperatures, and strong space radiation performance, which reduces weight while ensuring the reliability of protective materials in space applications.

[0006] The technical solution provided by the present invention is as follows:

[0007] In a first aspect, a space-grade energetic protection structural plate includes a polymer matrix material and an impact response agent, wherein the mass percentage of the polymer matrix material is 80% to 95%, and the mass percentage of the impact response agent is 5% to 20%.

[0008] In combination with the first aspect, the polymer matrix material is polyimide resin.

[0009] In combination with the first aspect, the impact response agent is selected from at least one of 5,5'-biquatrazolium-1,1'-dioxadihydroxyammonium or trinitrotoluene; preferably, the median particle size D50 of the impact response agent is 20 to 100 μm.

[0010] In combination with the first aspect, the impact response agent includes a high-energy oxidant and a metastable active material, the high-energy oxidant is selected from at least one of manganese dioxide, ferric oxide, copper oxide or potassium permanganate; the metastable active material is selected from at least one of aluminum powder, magnesium powder or boron powder; preferably, the median particle size D50 of the high-energy oxidant is 1 to 100 μm, and the median particle size D50 of the metastable active material is 0.1 to 150 μm.

[0011] In a second aspect, a method for preparing an aerospace-grade energetic protection structural plate comprises:

[0012] Adding polyimide resin into an organic solvent and stirring thoroughly until dissolved;

[0013] adding an impact response agent to the polyimide solution and stirring and dispersing the solution;

[0014] After the impact response agent is dispersed, the system temperature is increased to volatilize the organic solvent;

[0015] After the organic solvent is evaporated, the generated solid material is dried;

[0016] The dried solid material is crushed and a mold release agent is applied to the mold surface, and then the solid material is placed in the mold;

[0017] The mold is preheated and pressure is applied to the material for pre-pressing during preheating;

[0018] The preheated and pre-pressed material is pressed into shape to reach the set density requirement, and then the temperature is continued to rise to cross-link and solidify the polymer;

[0019] After the material in the mold is cooled, the pressure is released and the mold is demolded to obtain a space-grade energetic protective structure plate.

[0020] In combination with the second aspect, the step of preheating the mold and applying pressure to the material for pre-pressing treatment during preheating is specifically: raising the temperature of the mold to 70-80°C for preheating treatment within 5 minutes, applying 3-5MPa pressure to the material for pre-pressing treatment during preheating, and the pre-pressing time is 2-4 minutes.

[0021] In combination with the second aspect, the step of pressing the preheated and pre-pressed material into a shape to achieve the set density requirement, and then continuing to heat up to perform polymer cross-linking and curing is specifically as follows: heating to 150-170°C within 10 minutes, using a vacuum hydraulic press to perform pressing and molding under the conditions of 10-25 MPa and holding time of 5-10 minutes to achieve the set density requirement; then continuing to heat up to 200-230°C and keeping warm for 20-30 minutes to perform polymer cross-linking and curing.

[0022] The aerospace-grade energetic protection structural plate and the preparation method thereof provided by the present invention have the following beneficial effects:

[0023] (1) The present invention provides an aerospace-grade energetic protection structure plate and a preparation method thereof. By selecting a base material and an impact response material, the energetic protection structure plate can be provided with good mechanical properties. The impact response material can be locally detonated in a directional manner during a high-speed impact to provide active protection against space debris, thereby improving the protective effect of the non-metallic protection structure plate. The protective effect under high-speed impact is better than that of 2A12 aluminum alloy of the same thickness.

[0024] (2) The present invention provides a space-grade energetic protective structural plate and a preparation method thereof, wherein the base material is a polyimide. This type of material has a strong ability to resist space radiation and can greatly improve the tolerance of polymer protective materials to space particles such as electrons and protons, thereby meeting the requirements for the long life of spacecraft. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a physical picture of the aerospace-grade protective structural plate of the present invention;

[0026] Figure 2 Diagram of the perforation diameter of the protected plate when the aerospace-grade protective structural plate (Figure A) and the aluminum plate are used as the protective plate (Figure B) of the present invention;

[0027] Figure 3 This is a physical picture of the aerospace-grade protective structural plate (compression standard sample) of the present invention after 30 high and low temperature impacts (-196°C to 300°C);

[0028] Figure 4 The aerospace-grade protective structural plate (compressed standard sample) of the present invention is 1×10 7 Actual picture after rad(Si) irradiation. DETAILED DESCRIPTION

[0029] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.

[0030] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0031] The present invention provides an aerospace-grade energetic protection structural plate, comprising a polymer matrix material and an impact response agent; the mass percentage of the impact response agent is 5% to 20%, and the mass percentage of the polymer matrix material is 80% to 95%. The surface density of the aerospace-grade energetic protection structural plate is (0.6 to 1.3) g / cm 2 , compression strength ≥90MPa, 5% thermal decomposition temperature ≥250℃, total radiation dose of space cobalt source ≥10 7 rad(Si).

[0032] In the present invention, the polymer matrix material is a polyimide resin, and the polyimide resin is a soluble biphenyl polyimide with a number average molecular weight of 80,000 to 160,000. The specific gravity of the matrix material has a great influence on the overall structure of the protective material. While playing an active protective role, the content of the matrix material should be increased as much as possible to ensure that the protective material has good strength and tolerance to space environment.

[0033] In the present invention, the impact response agent is a gas-generating impact response agent, selected from at least one of 5,5'-biquatrazol-1,1'-dioxadihydroxyammonium or trinitrotoluene; the purity is ≥99wt%, and the median particle size D50 is 20-100μm.

[0034] In the present invention, the impact response agent is a heat-generating impact response agent, including a high-energy oxidant and a metastable active material, the high-energy oxidant is selected from at least one of manganese dioxide, ferric oxide, copper oxide or potassium permanganate; the purity of the high-energy oxidant is ≥99wt%, and the median particle size D50 is 1 to 100μm; the metastable active material is selected from at least one of aluminum powder, magnesium powder or boron powder; the purity of the metastable active material is ≥99wt%, and the median particle size D50 is 0.1 to 150μm. The dosage ratio of the high-energy oxidant and the metastable active material is determined according to the ratio of the two when the chemical reaction is complete. When a heat-generating impact response agent is used, the 5% thermal decomposition temperature of the protective structure plate reaches above 350°C.

[0035] The inventors have found that the particle size of the metastable active material has an important influence on the application safety and formability of the energetic protective structure plate; if the particle size is too small and below the allowable range, the material will catch fire when it is hit at high speed or when static load pressure is applied due to its high sensitivity; if the particle size is too large and exceeds the allowable range, the formability of the protective structure plate material will deteriorate during the pressing process, resulting in a decrease in the protective effect of the material.

[0036] In the above technical solution, the high-energy oxidant and metastable active material in the gas-generating impact response agent or the heat-generating impact response agent can slow down the impact speed through chemical reaction directional detonation when subjected to high-speed impact; polyimide is used as the matrix material to improve the structural plate's resistance to space radiation.

[0037] The present invention also provides a method for preparing a space-grade energetic protection structural plate, comprising the following steps:

[0038] (1) Weighing a polyimide resin and an organic solvent in a mass ratio of 1:(3-7);

[0039] (2) Add the weighed polyimide resin to the organic solvent and stir thoroughly. If necessary, heating can be used to accelerate the dissolution of the polyimide. If stirring and heating are turned on, the heating temperature is 40 to 50° C. and the stirring speed is adjusted to 80 to 120 r / min.

[0040] (3) After the polyimide is fully dissolved, the impact response agent is added, the mixed system is heated to 50-80° C., and slowly stirred to uniformly disperse the impact response agent;

[0041] (4) After the dispersion is completed, the system temperature is raised to 140-180° C. to allow the organic solvent to evaporate slowly;

[0042] (5) After the organic solvent is evaporated, the solid material is placed in an oven at 70 to 100° C. and dried for 2 to 4 hours;

[0043] (6) using a plastic roller to crush the dried solid material and apply a mold release agent to the mold surface, and then placing the solid material in a mold of a specified shape; the mold release agent includes but is not limited to a silicone mold release agent or a polytetrafluoroethylene mold release agent, etc.;

[0044] (7) Raise the temperature of the mold to 70-80° C. within 5 minutes for preheating, and apply a pressure of 3-5 MPa to the material for pre-pressing for 2-4 minutes.

[0045] (8) heating to 150-170° C. within 10 minutes, using a vacuum hydraulic press to perform compression molding under the conditions of 10-25 MPa and holding time of 5-10 minutes to achieve the set density requirement; further heating to 200-230° C., holding temperature for 20-30 minutes, and cross-linking and curing the polymer;

[0046] (9) Cool the material in the mold to below 50°C for pressure relief and demolding.

[0047] Example

[0048] Example 1

[0049] (1) Weigh 150 g of polyimide resin and add it into a beaker containing 450 g of acetone;

[0050] (2) Start stirring and heating, the heating temperature is 40°C, and the stirring speed is 100 r / min;

[0051] (3) After the polyimide is fully dissolved, the stirring speed is reduced to 20 r / min and 20 g of manganese dioxide (purity ≥ 99 wt %, median particle size D50 of 1 μm) and 10 g of aluminum powder (purity ≥ 99 wt %, median particle size D50 of 100 μm) are added, and the mixture is heated to 60° C. to uniformly disperse the components;

[0052] (4) Stir and disperse for about 5 minutes, and then raise the temperature to 140°C to allow the organic solvent to evaporate slowly;

[0053] (5) After the solvent evaporates, the solid mixture is placed in an oven at 80° C. for 4 hours for drying;

[0054] (6) crushing the dried mixture using a plastic roller, applying a polytetrafluoroethylene release agent to the mold, and then placing it in a mold of a specified shape;

[0055] (7) Raise the temperature of the mold to 80°C within 5 minutes for preheating treatment, and apply a pressure of 3 MPa to the material for pre-pressing treatment during preheating, and the pre-pressing time is 4 minutes;

[0056] (8) heating to 170° C. within 10 minutes, under a pressure of 15 MPa, and holding pressure for 10 minutes, using a vacuum hydraulic press to perform compression molding to achieve a set density requirement; further heating to 230° C., holding temperature for 20 minutes, and cross-linking and curing the polymer;

[0057] (9) Cool the material in the mold to below 50°C for pressure relief and demolding. See the actual picture. Figure 1 .

[0058] In order to verify the protective effect of aerospace-grade energetic protective structural panels and their reliability in space applications, the thickness, surface density, thermal decomposition temperature and compression performance of the protective panels were tested, and 30 high and low temperature shocks (-196℃~300℃), 1×10 7 rad(Si) total dose irradiation test. The thickness and surface density test results are shown in Table 1, the thermal decomposition temperature test results are shown in Table 2, the compression performance test results are shown in Table 3, and the perforation diameter test results are shown in Table 4 and Figure 2 The appearance of the protective plate after high and low temperature impact is as shown in Figure 3 As shown, the appearance is intact, without cracks, deformation and other damage; the appearance of the protective plate after total dose irradiation is as follows Figure 4 As shown, the color has become slightly darker and the appearance is intact, with no cracks, deformation or other damage.

[0059] Table 1 Thickness and surface density test results

[0060]

[0061] Table 2 Thermal decomposition temperature test results

[0062]

[0063] Table 3 Compression performance test results

[0064]

[0065] Table 4 Perforation diameter test results

[0066]

[0067] Example 2

[0068] (1) Weigh 150 g of polyimide resin and add it into a beaker containing 450 g of acetone;

[0069] (2) Start stirring and heating, the heating temperature is 40°C, and the stirring speed is 100 r / min;

[0070] (3) After the polyimide is fully dissolved, the stirring speed is reduced to 20 r / min and 20 g of ferric oxide (purity ≥ 99 wt %, median particle size D50 of 0.5 μm) and 10 g of magnesium powder (purity ≥ 99 wt %, median particle size D50 of 150 μm) are added, and the mixture is heated to 60° C. to uniformly disperse the components;

[0071] (4) Stir and disperse for about 5 minutes, and then raise the temperature to 140°C to allow the organic solvent to evaporate slowly;

[0072] (5) After the solvent evaporates, the solid mixture is placed in an oven at 80° C. for 4 hours for drying;

[0073] (6) crushing the dried mixture using a plastic roller, applying a polytetrafluoroethylene release agent to the mold, and then placing it in a mold of a specified shape;

[0074] (7) Raise the temperature of the mold to 80°C within 5 minutes for preheating treatment, and apply a pressure of 3 MPa to the material for pre-pressing treatment during preheating, and the pre-pressing time is 4 minutes;

[0075] (8) heating to 170° C. within 10 minutes, under a pressure of 15 MPa, and holding pressure for 10 minutes, using a vacuum hydraulic press to perform compression molding to achieve a set density requirement; further heating to 230° C., holding temperature for 20 minutes, and cross-linking and curing the polymer;

[0076] (9) Cool the material in the mold to below 50°C for pressure relief and demolding.

[0077] The surface density, thermal decomposition temperature and compression performance of the protective plate were tested, and 30 high and low temperature impacts (-196℃~300℃), 1×10 7 Rad(Si) total dose irradiation test. Surface density is 0.88g / cm 2 ; 5% thermal decomposition temperature is 502℃; 15% strain compressive stress before irradiation is 135MPa, and 15% strain compressive stress after irradiation is 139MPa; after high and low temperature impact, the appearance of the protective plate is intact, without cracking, deformation and other damage; after total dose irradiation, the appearance of the protective plate is slightly darker in color, and the appearance is intact, without cracking, deformation and other damage.

[0078] Example 3

[0079] (1) Weigh 150 g of polyimide resin and add it into a beaker containing 450 g of acetone;

[0080] (2) Start stirring and heating, the heating temperature is 40°C, and the stirring speed is 100 r / min;

[0081] (3) After the polyimide is fully dissolved, the stirring speed is reduced to 20 r / min and 10 g of 5,5'-biquatrazol-1,1'-dioxadihydroxyammonium (purity ≥ 99 wt %, median particle size D50 90 μm) is added, and the mixture is heated to 60° C. to uniformly disperse the components;

[0082] (4) Stir and disperse for about 5 minutes, and then raise the temperature to 140°C to allow the organic solvent to evaporate slowly;

[0083] (5) After the solvent evaporates, the solid mixture is placed in an oven at 80° C. for 4 hours for drying;

[0084] (6) crushing the dried mixture using a plastic roller, applying a polytetrafluoroethylene release agent to the mold, and then placing it in a mold of a specified shape;

[0085] (7) Raise the temperature of the mold to 80°C within 5 minutes for preheating treatment, and apply a pressure of 3 MPa to the material for pre-pressing treatment during preheating, and the pre-pressing time is 4 minutes;

[0086] (8) heating to 170° C. within 10 minutes, under a pressure of 15 MPa, and holding pressure for 10 minutes, using a vacuum hydraulic press to perform compression molding to achieve a set density requirement; further heating to 230° C., holding temperature for 20 minutes, and cross-linking and curing the polymer;

[0087] (9) Cool the material in the mold to below 50°C for pressure relief and demolding.

[0088] The surface density, thermal decomposition temperature and compression performance of the protective plate were tested, and 30 high and low temperature shocks (-196℃~150℃), 1×10 7 Rad(Si) total dose irradiation test. Surface density is 0.76g / cm 2 ; 5% thermal decomposition temperature is 278℃; 15% strain compressive stress before irradiation is 160MPa, and 15% strain compressive stress after irradiation is 167MPa; after high and low temperature impact, the appearance of the protective plate is intact, without cracking, deformation and other damage; after total dose irradiation, the appearance of the protective plate is slightly darker in color, and the appearance is intact, without cracking, deformation and other damage.

[0089] Comparative Example

[0090] Comparative Example 1

[0091] Comparative Example 1 is consistent with Example 1, except that the metastable active material is aluminum powder with a median particle size D50 of 10 nm. When the protective structure plate material is subjected to quasi-static compression, the material catches fire.

[0092] Comparative Example 2

[0093] Comparative Example 2 is consistent with Example 1, except that the metastable active material is aluminum powder with a median particle size D50 of 400 μm. The mechanical properties of the protective structure plate material after pressing are poor, and the material will crack before reaching 15% strain.

[0094] Comparative Example 3

[0095] Comparative Example 3 is consistent with Example 1, except that the impact response agent is 30g of manganese dioxide and 15g of aluminum powder. The mechanical properties of the protective structure plate material after compression molding are poor, and the material will crack before reaching 15% strain.

[0096] Comparative Example 4

[0097] Comparative Example 4 is consistent with Example 1, except that the impact response agent is 4g of manganese dioxide and 2g of aluminum powder. After the protective structural plate material is subjected to high-speed impact, the perforation diameter of the protected plate becomes significantly larger, and an excellent protective effect is not achieved.

[0098] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0099] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.

Claims

1. An aerospace grade energetic protection structural plate, characterized in that: It comprises a polymer matrix material and an impact response agent, wherein the mass percentage of the polymer matrix material is 80% to 95%, and the mass percentage of the impact response agent is 5% to 20%.

2. The aerospace grade energetic protection structural plate according to claim 1, characterized in that: The polymer matrix material is polyimide resin.

3. The aerospace grade energetic protection structural plate according to claim 1, characterized in that: The impact response agent is selected from at least one of 5,5'-bi-tetrazole-1,1'-dioxadihydroxyammonium or trinitrotoluene.

4. The aerospace grade energetic protection structural plate according to claim 3, characterized in that: The median particle size D50 of the impact response agent is 20 to 100 μm.

5. The aerospace grade energetic protection structural plate according to claim 1, characterized in that: The impact response agent includes a high-energy oxidant and a metastable active material, wherein the high-energy oxidant is selected from at least one of manganese dioxide, ferric oxide, copper oxide or potassium permanganate; and the metastable active material is selected from at least one of aluminum powder, magnesium powder or boron powder.

6. The aerospace grade energetic protection structural plate according to claim 5, characterized in that: The median particle size D50 of the high-energy oxidant is 1 to 100 μm.

7. The aerospace grade energetic protection structural plate according to claim 5, characterized in that: The median particle size D50 of the metastable active material is 0.1 to 150 μm.

8. A method for preparing the aerospace-grade energetic protection structural plate according to any one of claims 1 to 7, characterized in that: include: Adding polyimide resin into an organic solvent and stirring thoroughly until dissolved; adding an impact response agent to the polyimide solution and stirring and dispersing the solution; After the impact response agent is dispersed, the system temperature is increased to volatilize the organic solvent; After the organic solvent is evaporated, the generated solid material is dried; The dried solid material is crushed and a mold release agent is applied to the mold surface, and then the solid material is placed in the mold; The mold is preheated and pressure is applied to the material for pre-pressing during preheating; The preheated and pre-pressed material is pressed into shape to reach the set density requirement, and then the temperature is continued to rise to cross-link and solidify the polymer; After the material in the mold is cooled, the pressure is released and the mold is demolded to obtain a space-grade energetic protective structure plate.

9. The method for preparing aerospace-grade energetic protection structural panels according to claim 8, characterized in that: The step of preheating the mold and applying pressure to the material for pre-pressing treatment during preheating is specifically: raising the temperature of the mold to 70-80°C for preheating treatment within 5 minutes, applying 3-5MPa pressure to the material for pre-pressing treatment during preheating, and the pre-pressing time is 2-4 minutes.

10. The method for preparing aerospace-grade energetic protection structural panels according to claim 8, characterized in that: The step of pressing the preheated and pre-pressed material to achieve the set density requirement, and then continuing to heat up to perform polymer cross-linking and curing is specifically as follows: heating to 150-170° C. within 10 minutes, using a vacuum hydraulic press to perform pressing and molding under the conditions of 10-25 MPa and holding time of 5-10 minutes to achieve the set density requirement; and then continuing to heat up to 200-230° C. and holding the temperature for 20-30 minutes to perform polymer cross-linking and curing.